Comparative Usability Study of a Newly Created Patient-Centered Tool and Medicare.gov Plan Finder to Help Medicare Beneficiaries Choose Prescription Drug Plans. (March 2019) - Stults, Cheryl D; Fattahi, Sayeh; Meehan, Amy; Bundorf, M Kate; Chan, Albert S; Pun, Ting; Tai-Seale, Ming
Introduction: In response to reported difficulties in selecting a Medicare Part D prescription drug plan, we designed a patient-centered online Part D plan selection tool (CHOICE1.0) to simplify the selection process and to provide personalized, expert recommendations. Methods: This ethnographic comparative usability study observed 44 patients using the first version of the tool during Medicare 2016 Open Enrollment. Participants were observed as they chose their drug plan usingMedicare.gov and 1 of 3 versions of CHOICE1.0 that varied in amount of expert guidance. Descriptive statistics were used to analyze exit survey data. The observations were video-recorded, and field notes were analyzed thematically. Results: Participants were significantly more satisfied with CHOICE1.0 for choosing a plan, understanding information, and ease of use compared toMedicare.gov . Those using expert versions of CHOICE1.0 were more likely to indicate their intention to switch plans than those usingMedicare.gov, though they wanted to know the source and content. Conclusion: The more patient-centered prescription drug choice tool improved user experience and enabled users to choose plans more consistent with expert recommendations.